The EU Soft Power in the Global Equilibrium - A. Baykov (Vestnik MGIMO-Universiteta)
The paper analyzes the basic parameters of the soft power of the European Union in the context of the effectiveness of its foreign policy and comparison with the efforts of Russia's own resources capacity of non-violent political influence. To solve this purpose the author dissects the basic interpretation soft power, reviews the criteria to measure the effectiveness foreign policy, highlights the existing scholarly discussion regarding the applicability, relevance and accuracy of the concepts of hard and soft power in applied policy analysis. Particular attention is paid to the problem of trust in international relations in general and in the relations between Russia and the EU in particular. The presence of trust in international relations constitutes a prerequisite to solve any problems for foreign policy. Analyzing the practical expression of the basic values of Western European countries and Russia the article concludes that the efficiency of 'soft power' strategies exercised both by Russia and the EU vis-à-vis each other is rather low. The multi-faceted relations between Russia and the European Union with closely interwoven national interests of different countries do not make these relationships easier whereas a whole array of historical and psychological problems do not add trust. Therefore, it is reasonable to opt for formalized dialogue institutions. In conclusion, the author provides recommendations for medium-and long-term prospects of the bilateral relations.